Administrasi dan Supervisi Pendidikan Evaluasi Kinerja Guru - Fernanda, Diska; Indriani, Nova; Alhikma, Alika (UNIVERSITAS SERAMBI MEKKAH, 2025)
This research aims to analyze the results of a study of ten articles discussing educational supervision and evaluation of teacher performance, especially at the elementary school level. The results of the analysis show that effective supervision, whether academic, administrative, collaborative, or technology-based, has a significant contribution to improving the quality of learning and teacher professionalism. Academic supervision helps teachers strengthen pedagogical competencies through better lesson planning and implementation, while administrative supervision ensures efficiency in managerial tasks. A collaborative approach and use of technology accelerates the evaluation process and encourages innovation in teaching. Supporting factors, such as transformational leadership, positive school culture, and motivation, also play an important role in successful supervision. Based on these findings, it is recommended to implement integrated supervision, increase technology-based training, and develop a collaborative work culture in elementary schools to support continuous improvement in teacher performance.